The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/15538605.2017.1310007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Flexibility and Self-Compassion in Gay and Heterosexual Men: How They Relate to Childhood Memories, Shame, and Depressive Symptoms

Abstract: This study explores differences between gay men (N = 53) and heterosexual men (N = 52) regarding memories of shame events and of warmth and safeness experiences with parents during childhood and adolescence, self-compassion, psychological flexibility, internal shame and depression. Also, it aims to explore whether psychological flexibility and selfcompassion play a role in the association between these memories and internal shame and depressive symptoms. Results confirmed the mediating role of psychological fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Puckett et al (2015) found that self-criticism partially mediated the relationship between internalized sexual stigma and negative mental health outcomes in a sexual minority sample. Matos et al (2017) found that sexual minority men seem to be less self-compassionate than heterosexual men, and this self-relating process emerged to be more strongly correlated with internal shame and depression than the heterosexual counterparts.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Puckett et al (2015) found that self-criticism partially mediated the relationship between internalized sexual stigma and negative mental health outcomes in a sexual minority sample. Matos et al (2017) found that sexual minority men seem to be less self-compassionate than heterosexual men, and this self-relating process emerged to be more strongly correlated with internal shame and depression than the heterosexual counterparts.…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, several studies have investigated the negative impact of self-criticism on sexual minority people's wellbeing (Greene & Britton, 2015;Matos et al, 2017). Puckett et al (2015) found that self-criticism partially mediated the relationship between internalized sexual stigma and negative mental health outcomes in a sexual minority sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…My MDMA experience has also facilitated greater self-compassion and psychological flexibility, which have been especially helpful in terms of adapting to, easing, and coexisting with the chronic dissonance I felt between my sexual and ethnic identities while attempting to navigate my ethnic community and LGBTQIA+ spaces. Indeed, self-compassion and psychological flexibility have been shown to promote mental wellness in sexual minorities by ameliorate internalized homophobia (Beard, Eames, & Withers, 2017;Matos, Carvalho, Cunha, Galhardo, & Sepodes, 2017).…”
Section: Final Thoughtsmentioning
confidence: 99%
“…As the child develops, the memories of sexual trauma emerge that he was sexually abused with feelings contradictory between the sense of pleasure and happiness and the shame, guilt and dejection and other symptoms like physical symptoms, depression and PTSD including gay behaviors [43][44][45].…”
Section: Discussionmentioning
confidence: 99%